2021
DOI: 10.3390/polym13111745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mechanical Properties of PMMA Disks for Digitally Designed Dentures

Abstract: In this study, the physical properties of a custom block manufactured using a self-polymerizing resin (Custom-block), the commercially available CAD/CAM PMMA disk (PMMA-disk), and a heat-polymerizing resin (Conventional PMMA) were evaluated via three different tests. The Custom-block was polymerized by pouring the self-polymerizing resin into a special tray, and Conventional PMMA was polymerized with a heat-curing method, according to the manufacturer’s recommended procedure. The specimens of each group were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…The absorbed water enters between the layers, and then the water molecules are diffused into the resin's polymer, which allows interpolymeric spaces to be filled with water, forcing the polymer chain away from other chains [1,29,30]. This phenomenon might adversely affect the layering interface, which leads to swelling of the resin and separates the printed layers [13,26]. The presence of voids in 3D-printed resins was confirmed with scanning electron microscopy [1].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The absorbed water enters between the layers, and then the water molecules are diffused into the resin's polymer, which allows interpolymeric spaces to be filled with water, forcing the polymer chain away from other chains [1,29,30]. This phenomenon might adversely affect the layering interface, which leads to swelling of the resin and separates the printed layers [13,26]. The presence of voids in 3D-printed resins was confirmed with scanning electron microscopy [1].…”
Section: Discussionmentioning
confidence: 91%
“…Once the specimens were weighed for sorption, they were dried to achieve a constant mass (m3); the drying process was similar to the method used for m1 determination. The solubility values of the specimens were obtained using the following formula: (Wsl = (m3 − m1)/specimen volume (V)) [12,13].…”
Section: Water Sorption/solubility and Translucency Measurements [T1]mentioning
confidence: 99%
See 1 more Smart Citation
“…Titles irrelevant to the research question, duplicate titles, and publications in languages other than English were excluded This process yielded 25 studies that were further scrutinized to ensure meeting inclusion criteria. At the end, nine studies[ 13 23 , 27 28 29 30 31 32 33 ] were included for data extraction and analysis. Table 1 presents a summary of extracted data.…”
Section: R Esultsmentioning
confidence: 99%
“…Figure 2 summarizes the risk of bias for the included studies. Out of the nine included studies, six[ 13 23 , 28 29 30 31 ] showed medium risk, two[ 27 32 ] showed high risk of bias, and one[ 33 ] showed low risk of bias. The risks of bias reported were mainly due to missing information regarding sample size calculation and blinding of examiners.…”
Section: R Esultsmentioning
confidence: 99%